Why we don't eat as intended: moderators of the short-term intention-behaviour relation in food intake - Aulbach, Matthias Burkard; Alebeek, Hannah van; Jones, Christopher; Blechert, Jens (British journal of health psychology, 2024)
Objectives: A healthy diet is essential for preventing chronic disease and promoting overall health. Translating one's intention to eat healthy into actual behaviour has, however, proven difficult with a range of internal and contextual factors identified as driving eating behaviour. Design We leverage Temporal Self-Regulation Theory to examine these momentary determinants' direct and moderating effects on the intention-behaviour relation with Ecological Momentary Assessment (EMA). Methods: Eighty-seven healthy participants (mage = 24.1 years; 59 women, 28 men) reported, 5 times daily for 10 weekdays, their intentions to stick to a self-set dietary restriction goal for the next 3 hr, the goal congruency of their eating behaviour in the past 3 hr, and a range of factors potentially influencing food intake, such as stress, emotions and environmental eating cues. Results: Two-part multilevel modelling revealed that craving, availability of goal-incongruent foods, social eating cues, giving in to other temptations and weaker momentary intentions directly increased the risk and severity of goal-incongruent intake within the next 3 hr. Social cues, stress and craving further influence behaviour through altering intention implementation. Conclusions Results imply that people regularly fail to implement intentions for 3-hr periods and that a range of factors influences this, both directly and by disrupting intentional processes. While for some barriers, fostering strong intentions throughout the day could be beneficial, others require different strategies for dietary adherence.
Online veröffentlicht: 30. Januar 2024
Gesehen am 10.10.2024